2009
DOI: 10.1523/jneurosci.0233-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

A Retrograde Neuronal Survival Response: Target-Derived Neurotrophins Regulate MEF2D and bcl-w

Abstract: Survival and maturation of dorsal root ganglia sensory neurons during development depend on target-derived neurotrophins. These target-derived signals must be transmitted across long distances to alter gene expression. Here, we address the possibility that long-range retrograde signals initiated by target-derived neurotrophins activate a specialized transcriptional program. The transcription factor MEF2D is expressed in sensory neurons; we show that expression of this factor is induced in response to target-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 71 publications
(90 reference statements)
1
60
0
Order By: Relevance
“…S5), indicating that the effects of BDNF do not reflect retrograde signaling from axons to the nucleus. Importantly, previous studies using Campenot chambers, where the distance between axons and cell bodies is 1 mm, have shown that neurotrophins can convey signals from axons to the nucleus in peripheral system neurons within the time course of our experiments (22,23).…”
Section: Resultsmentioning
confidence: 71%
“…S5), indicating that the effects of BDNF do not reflect retrograde signaling from axons to the nucleus. Importantly, previous studies using Campenot chambers, where the distance between axons and cell bodies is 1 mm, have shown that neurotrophins can convey signals from axons to the nucleus in peripheral system neurons within the time course of our experiments (22,23).…”
Section: Resultsmentioning
confidence: 71%
“…Further, the technical challenge of delivering interfering molecules (i.e., siRNAs) efficiently into neurons has also been only more recently addressed. Existing literature suggests a role of ERK5 in neuronal development (Cundiff et al 2009), adult neurogenesis in hippocampus and the olfactory bulb Pan et al 2013), neuronal survival in both CNS and PNS (Watson et al 2001;Pazyra-Murphy et al 2009), and neuropathic pain in the spine (Obata et al 2007). A few studies have identified neurotrophins, including NGF, BDNF and NT-3 as major physiological activators of ERK5 in neurons (Watson et al 2001;Wang et al 2006b;Ohtsuka et al 2009;Yu et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…1). Addition of neurotrophins to distal axons, but not cell bodies, also enhances activation of the transcription factor MEF2D by a Trk-dependent ERK5 pathway (18). Together, ERK5 and MEF2D increase expression of the antiapoptotic protein bcl-w, MEF2D, and other retrograde response genes.…”
Section: Diverse Receptor Families Signal From Endosomes (Summarized Inmentioning
confidence: 96%
“…Difficulties in studying endosomal signaling in cells in primary culture or in intact animals include detection of signaling molecules, which are often expressed at low levels, and discrimination between plasma membrane and endosomal signaling events. Promising approaches include studies of mice expressing fluorescently tagged receptors (99) or lacking key endosomal signaling proteins (87), siRNA knockdown of signaling intermediates in neurons (18), use of innovative methods to isolate endosomal signaling complexes (4,55), and studies of agonists that selectively activate endosomal rather than plasma membrane signaling pathways (89)(90)(91).…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%